PRIMARY PRODUCTION PROCESSES IN ICE-FREE WATERS OF THE ROSS SEA (ANTARCTICA) DURING THE AUSTRAL SUMMER 1996 - Saggiomo, Vincenzo; Catalano, Giulio; MANGONI, OLGA; BUDILLON, Giorgio; CARRADA, Gian Carlo (2002)
During austral summer 1996 (January 11–February 10) oceanographic studies were conducted in the ice-free waters ofthe Ross Sea within the framework ofthe Italian National Programme for Antarctic Research (PNRA). Thirty-eight hydrological stations within 72.51–78.01S and 164.51E–175.01W were sampled. Size-fractionated photosynthetic pigments were measured at all stations, primary production was evaluated at 24 stations, and P vs. E measurements were carried out at 3 or 4 depths at 18 stations. In the open Ross Sea, integrated chlorophyll a (Chla) concentrations were between 15 and 102 mgm2 in the 0–100m layer, and primary production was between 124 and 638mgCm2 d1. Offshore waters were completely ice-free and the water column was only slightly stratified. However, phytoplankton biomass and production were relatively high wherever the Upper Mixed Layer (UML) was o30m deep. Hydrographic characters and phytoplankton distribution varied remarkably along the coastal waters ofTerra Nova Bay; during a late summer bloom, integrated primary production ranged between 620 and 2411mgCm2 d1. The dimensional composition ofphytoplankton communities and the Redfield ratio indicate that the Ross Sea was dominated by diatoms. The photosynthetic parameters measured suggest the importance ofthe depth and dynamics ofthe UML, where the integrated mean irradiance always exceeded the photosaturation index (Ek). However, occasionally different PB max and Ek were recorded even in apparently well-mixed water columns. The presence of turbulent cells in different layers of the photic zone or a weak wind-driven vertical mixing, which might induce different photosynthetic indexes, can thus be hypothesized. Simulated in situ primary production was well correlated with production calculated with the photosynthetic coefficients obtained from the P vs. E experiments. Our data could be used to construct models aimed at assessing primary production in the area studied.